Long-Term Lifestyle Intervention in Elderly With Metabolic Syndrome. (July 2019) - Chang, Shu-Hung; Chien, Nai-Hui; Yu, Ching-Yi
The purpose of this study was to examine the effects of a long-term community-based lifestyle intervention on the biochemical indicators and prevalence of metabolic syndrome among elderly adults. This was a randomized controlled trial in northern Taiwan from August 2013 to February 2015. Sixty-nine elderly adults participated in this study. There were three measurements. The experimental group participated in exercise and diet interventions. The control group participated in the exercise intervention. Repeated measurement and ANCOVA were performed to evaluate the effectiveness. After 18 months, body weight (1.06 kg), body mass index (1.21 kg/m 2 ), waist circumference (3.32 cm), blood pressure, and prevalence (30.4%) of metabolic syndrome were significantly reduced in all subjects. There were significant differences in waist circumference and high-density lipoprotein cholesterol between the two groups. This intervention can lower the indicators and prevalence of metabolic syndrome. Exercise and diet interventions could promote further metabolic changes.